Identification and mapping of the water-logged areas in Purba Medinipur part of Keleghai river basin, India: RS and GIS methods - Sahu, Abhay (International Journal of Advanced Geosciences, 2014)
The prime objective of this paper is to identify and mapping of the water-logged areas applying methods of Remote Sensing (RS) and Geographical Information System (GIS) in the part of Purba Medinipur district of Keleghai river basin, India. For this purpose, USGS Landsat 8 imagery (4th November, 2013) and topographical sheets (scale - 1:50,000; year - 1970) have been used here, processing through Arc GIS 9.3 and ERDAS Imagine 9.1, with field observations. A supervised classification of Landsat 8 imagery (2013) of the study area has been made after conversion of DN value to Top of Atmosphere (TOA) radiance value, and it is found that the amount of water-logged areas is 80-km2. Based on different maps, it is observed that the factors like relief, slope, embankment density and settlement density have disproportionate relationship and canal density has direct proportion with the spatial distribution of water-logged areas. Here, RS techniques like NDVI, NDWI and modified NDWI or NDMI have been followed to corroborate water-logged areas and finally to understand the relevance of these techniques toward mapping of the water-logged areas, a Correlation Matrix has been prepared using SPSS 20 software and in result they are acceptable for an understanding on water-logged areas as values of them are significantly correlated with canal density. Keywords: Water-Logged Areas, Low-Lying Areas, Canal Density, RS Techniques, Correlation Matrix.